2013
DOI: 10.3109/0886022x.2013.811345
|View full text |Cite
|
Sign up to set email alerts
|

Is colchicine therapy effective in all patients with secondary amyloidosis?

Abstract: Objective: Although colchicine is effective on prevention and regression of amyloidosis in many cases, rate of unresponsiveness to colchicine therapy is not too low. However, there is no sufficient data about which factors effect to response of colchicine therapy on regression of amyloidosis. Materials and methods: 24 patients with renal amyloidosis were enrolled into the study. The patients were divided in two groups according to urinary protein excretions: non-nephrotic stage (14/24) and nephrotic stage (10/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…The disease is common in Mediterranean countries, and the incidence of the disease has been reported as 1/200 in Ashkenazi Jews and 1/1000 in Turks [2]. Colchicine treatment has been shown to be effective in preventing the development of amyloidosis and in reducing proteinuria [3]. Subclinical inflammation can also be observed in FMF.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is common in Mediterranean countries, and the incidence of the disease has been reported as 1/200 in Ashkenazi Jews and 1/1000 in Turks [2]. Colchicine treatment has been shown to be effective in preventing the development of amyloidosis and in reducing proteinuria [3]. Subclinical inflammation can also be observed in FMF.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent large cohort studies confirmed that colchicine efficacy in amyloidosis is limited to cases of inflammation-induced nephropathic amyloidosis without major cardiovascular involvement [81], and particularly to the early proteinuric stage of amyloidosis due to FMF [82]. Colchicine dose increase to 2.5 --3 mg/day can be guided by levels of SAA, the precursor protein of FMF-related amyloid substance, which is predominantly elevated in patients with family history of FMF, persistent proteinuria, M694V homozygosity and high CRP [83].…”
Section: Colchicine In Systemic Amyloidosismentioning
confidence: 94%
“…[ 8 ] However, its beneficial effect in the other causes of AA amyloidosis is not clear. [ 9 ] In addition, case reports and small case series involving patients with FMF and other rheumatic diseases have reported some success with various immunosuppressives and immunomodulators such as azathioprine, [ 10 ] chlorambucil, [ 11 ] methotrexate, [ 12 ] interferon-alpha, [ 13 ] and cyclophosphamide. [ 14 ] In the last decade, biologic agents targeting proinflammatory cytokines such as tumor necrosis factor alpha (TNF-α), interleukin (IL)-1, and IL-6 have been tried in patients with AA amyloidosis.…”
Section: Introductionmentioning
confidence: 99%